Migration and inheritance practices in the Bolivian Altiplano - Anne Michels (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Most theoretical approaches to inheritance assume that parents are the key actors of bequest decisions. However, in a context of important migration, children may play an active role in the inheritance process. Based on a unique data set collected at both ends of the migration link in Bolivia, we are able to show that migrant children significantly influence the way inheritance is distributed through their decision to accept or refuse their share of inheritance. This decision is not only influenced by the migrants need for economic security but also by the transaction costs associated to land ownership. Yet, land inheritance is not completely driven by the demand for inheritance of the children. Parents continue to play an important role and the identity of the person responsible for the migration decision emerges as an important determinant of their bequest decision.
Keywords: D10; O12; O15; Q15; 330; land access; inheritance; migration; transaction costs